Avaliação do potencial efeito ansiolítico do aroma de laranja doce (Citrus sinensis) - Goes, Tiago Costa (2011)
The aim of this study was to evaluate the potential anxiolytic effect of sweet orange aroma in healthy volunteers submitted to an anxiogenic situation. For this purpose, forty male volunteers, aged between 18 and 30 years, were allocated to five different groups (n=8) for the inhalation of sweet orange essential oil (test aroma: 2.5, 5 or 10 drops), Melaleuca alternifolia essential oil (control aroma: 2.5 drops) or distilled water (non-aromatic control: 2.5 drops). Immediately after inhalation, each volunteer was submitted to a model of anxiety, the video-monitored version of the Stroop Colour Word Test. Psychological parameters (state-anxiety, subjective tension, tranquilization and sedation) and physiological parameters (heart rate and gastrocnemius electromyogram) were evaluated before the inhalation period and before, during and after the test. The results of the psychological parameters were analyzed by Friedman s ANOVA, for each treatment group, followed by Tukey-type test for post hoc comparisons. The results of the physiological parameters were analyzed using a two-factor analysis of variance (ANOVA) for repeated measures followed by Tukey s test for post hoc comparisons. All significance tests were two-tailed and were performed at the 5% significance level. It s worth calling attention to the fact that the treatment s effect is revealed by the lack of significant alterations in the observed parameters throughout the test. Unlike the control groups, the individuals exposed to the test aroma in the doses of 2.5 drops and 10 drops did not present significant alterations (p > 0.05) in state anxiety, subjective tension and tranquillity levels throughout the anxiogenic situation, revealing an anxiolytic activity of sweet orange essential oil. Physiological alterations along the test were not prevented in any treatment group, as has previously been observed for diazepam. Although more studies are needed to find out the clinical relevance of aromatherapy for anxiety disorders, the present results indicate an acute anxiolytic activity of sweet orange aroma, giving some scientific support to its use as a tranquilizer by aromatherapists.